The Health Consequences of Speaking Out - Rosemary Greaves; John K. McGlone (Social Medicine Publication Group, 2024)
People who speak out in the public interest, known as whistleblowers, often threaten vested interests. When whistleblowers suffer reprisals, as frequently occurs, the consequences for their health can be serious. Interviews with members of Whistleblowers Australia reveal that whistleblowers can experience a range of adverse psychological and physical effects, some of them quite serious. Whistleblowers use various methods to cope with these consequences, including telling their stories and seeking support from counsellors and others. Key words whistleblowing; health; coping; well-being